Comprehensive Search for GPCR Compounds which Can Enhance MafA and/or PDX-1 Expression Levels Using a Small Molecule Compound Library - Hideaki Kaneto; Atsushi Obata; Masashi Shimoda; Tomohiko Kimura; Yoshiyuki Obata; Tomoko Ikeda; Saeko Moriuchi; Shuhei Nakanishi; Tomoatsu Mune; Kohei Kaku (Journal of Diabetes Research)
It has been shown that chronic hyperglycemia gradually decreases insulin biosynthesis and secretion which is accompanied by reduced expression of very important insulin gene transcription factors MafA and PDX-1. Such phenomena are well known as β-cell glucose toxicity. It has been shown that the downregulation of MafA and/or PDX-1 expression considerably explains the molecular mechanism for glucose toxicity. However, it remained unknown which molecules can enhance MafA and/or PDX-1 expression levels. In this study, we comprehensively searched for G protein-coupled receptor (GPCR) compounds which can enhance MafA and/or PDX-1 expression levels using a small molecule compound library in pancreatic β-cell line MIN6 cells and islets isolated from nondiabetic C57BL/6 J mice and obese type 2 diabetic C57BL/KsJ-db/db mice. We found that fulvestrant and dexmedetomidine hydrochloride increased MafA, PDX-1, or insulin expression levels in MIN6 cells. We confirmed that fulvestrant and dexmedetomidine hydrochloride increased MafA, PDX-1, or insulin expression levels in islets from nondiabetic mice as well. Furthermore, these reagents more clearly enhanced MafA, PDX-1, or insulin expression levels in islets from obese type 2 diabetic db/db mice in which MafA and PDX-1 expression levels are reduced due to glucose toxicity. In conclusion, fulvestrant and dexmedetomidine hydrochloride increased MafA, PDX-1, or insulin expression levels in MIN6 cells and islets from nondiabetic mice and obese type 2 diabetic db/db mice. To the best of our knowledge, this is the first report showing some molecule which can enhance MafA and/or PDX-1 expression levels. Therefore, although further extensive study is necessary, we think that the information in this study could be, at least in part, useful at some point such as in the development of new antidiabetes medicine based on the molecular mechanism of β-cell glucose toxicity in the future.